Southeast asian medicinal plants as a potential source of antituberculosis agent - Sanusi, Shuaibu Babaji; Abu Bakar, Mohd Fadzelly; Mohamed, Maryati; Sabran, Siti Fatimah; Mainasara, Muhammad Murtala (Hindawi Publishing Corporation, 2017)
Despite all of the control strategies, tuberculosis (TB) is still a major cause of death globally and one-third of the world’s population is infected with TB. The drugs used for TB treatment have drawbacks of causing adverse side effects and emergence of resistance strains. Plant-derived medicines have since been used in traditional medical system for the treatment of numerous ailments worldwide. There were nine major review publications on antimycobacteria from plants in the last 17 years. However, none is focused on Southeast Asian medicinal plants. Hence, this review is aimed at highlighting the medicinal plants of Southeast Asian origin evaluated for anti-TB. This review is based on literatures published in various electronic database. A total of 132 plants species representing 45 families and 107 genera were reviewed; 27 species representing 20.5% exhibited most significant in vitro anti-TB activity (crude extracts and/or bioactive compounds 0–<10